Respons Pertumbuhan dan Produksi Tanaman Semangka (Citrullus vulgaris Schard.) terhadap Pemberian Giberelin dan Pupuk TSP - Zaura Makhliza; Ferry Ezra T. Sitepu; Haryati Haryati (Universitas Sumatera Utara, 2014)
The objective of this experiment is to determine the respons in growth and yield of watermelon(Citrullus vulgaris Schard.) to Gibberellins and TSP fertilizer. This experiment was conducted atland of Pasar I Street No. 89, Tanjung Sari, Medan with the level approximately ± 25 inabove sea level, starting from May to December 2013 using factorial randomized block design withtwo factor, i.e. gibberellin (0, 100, 200 and 300 ppm) and TSP fertilizer (60, 80and 100 g/plant). Parameter observed were plant height, days to flowering, weight of fruit andnumber of seed. The result showed that gibberellin concentration affect significantly to the numberof seed and weight of fruit and giving up to 200 ppm gibberellin treatment on fertilizer TSP 80g/plant significantly speed up the age of harvesting.Keywords : gibberellin, TSP fertilizer, watermelon